Biocompatibility and Nanotoxicity of Layered Two‐Dimensional Nanomaterials. Issue 1 (16th December 2016) - Kenry,; Lim, Chwee Teck
Abstract: Layered two‐dimensional (2D) nanomaterials, such as graphene, transition metal dichalcogenides (TMDs), layered metal oxides (LMOs), black phosphorus (BP), and hexagonal boron nitride (hBN), have attracted tremendous interest recently owing to their unique structural morphologies and outstanding physicochemical properties. Consequently, these nanomaterials have been actively explored for different biological and biomedical applications, such as tissue engineering, drug delivery, bioimaging, and biosensing. As increasing efforts have been focused on identifying the potential bioapplications of layered 2D nanomaterials, one of the fundamental aspects that is of considerable interest and ought to be studied in greater depth is their biocompatibility and nanotoxicity. In addition, as the elucidation and understanding of the physicochemical properties of this new class of nanomaterials are still in their infancy, information on both in vitro and in vivo biocompatibility and nanotoxicity is still scarce and remains poorly understood. As such, there is an immediate need to explore and establish the biocompatibility and nanotoxicological profiles of these nanomaterials in order to develop and optimize them for specific bioapplications. Here, in this Focus Review, we will provide a broad overview of recent advances on the biocompatibility and nanotoxicity of layered 2D nanomaterials. First, a wide range of established and emerging layered 2D nanomaterials actively investigated for bioapplications will be introduced. Next, the different physicochemical aspects governing the biocompatibility and nanotoxicity of these nanomaterials, such as lateral size, concentration, exposure time, number of layers, and chemical composition and surface functionalization, will be evaluated. Finally, we will summarize the review and provide our perspectives on the challenges and opportunities facing this important field. Abstract : Layered 2D nanomaterials have been extensively explored for biological and biomedical applications, such as tissue engineering, drug delivery, bioimaging, and biosensing. For such applications, some of the most important considerations that ought to be studied in great depth is their biocompatibility and nanotoxicity.